(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Organizations must maintain sustainable employee well-being while maintaining performance at a time of growing job demands, digital overload, and the erosion of work-life boundaries. This conceptual study investigates the potential of mindfulness, which is often characterized as present-moment, nonjudgmental awareness, as a long-term professional approach. The study offers a conceptual framework that links mindfulness practices to improved personal resources (emotional regulation, attention, resilience), which in turn lead to better mental health, a better work-life balance, and increased productivity. It does this by drawing on important theories (such as Conservation of Resources, Job Demands–Resources, Attention Restoration, and Self-Regulation) and a broad body of empirical and theoretical literature.The research presents mindfulness as a long-term corporate resource that supports workplace culture, sustainable performance, and employee resilience rather than only as a personal health tool. Future research directions and practical implications are highlighted.